Formulation of Calcium-Protein Capsule Supplements for Stunting Toddlers by Utilizing Leftover Milkfish Bones Production - Sarah Raisya Nurhaliza; Joseph Fide Anggi; Angel Christella; Aurelina Yunita Hess; Mazaya Salwa Nadhira; Iyan Sopyan (Universitas Sebelas Maret, 2025)
Stunting is a health problem in children due to chronic malnutrition. Stunting is characterized by failure of growth and development in children. If stunting occurs during the Golden Period (age 0-5 years), it can impact the child's brain cells, causing them not to grow optimally. Indonesia has a stunting prevalence of 36% and has not reached the WHO's expected level of below 20%. Milkfish bones (Chanos chanos) are the remaining processed products of the fishing industry that have not been maximally utilized and will generally be disposed of into the environment or reprocessed and used as animal feed. With the presence of calcium and protein in the milkfish's bones, the milkfish's bones can be utilized as capsule supplements to address stunting in toddlers. This research was conducted to determine milkfish bones' calcium and protein content and obtain the most suitable capsule supplement formulation for stunting. This research was carried out through several stages, such as making milkfish bone powder, formulating and making stunting capsule supplements, evaluating the preparation, and analyzing and concluding the research results. The calculation of the consumption capsule supplement dose uses the percentage of calcium and protein content determined by AAS and Kjeldahl, which is then multiplied by the total weight of the capsule. The capsule consumption frequency is determined to fulfill the calcium requirement. The dose analysis and calculation results indicate that toddlers aged 1-3 years can consume two capsules daily, which is equivalent to 264.96 mg calcium and 88.32 mg protein, while toddlers aged 4-8 can consume three capsules daily, which is equivalent to 397.44 mg calcium and 32.48 mg protein. The dosage is determined based on the daily calcium needs of toddlers, which is 700 mg for children aged 1-3 years and 1000 mg for children aged 4-8 years. Therefore, developing milkfish bones with their calcium and protein content into capsule supplements could address toddler stunting.